Understanding Citizen Science as a Participatory Approach in Public Health Research and Practice - Leah Marks; Samantha Rowbotham; Ben J. Smith; Sahibnoor K. Singh; Jo Mitchell; Yvonne Laird (Journal of Prevention and Health Promotion, 2026)
Citizen science approaches, which actively involve members of the public in scientific research, are increasingly gaining attention as a means of engaging community members in research and decision-making in public health. However, there is a lack of clarity around the extent to which citizen science can be considered to be distinct from other participatory research approaches in public health. In this conceptual article, we aimed to explore the conceptual and practical distinctions between citizen science and three established participatory research approaches used in public health: community-based participatory research, participatory action research, and co-design. We discuss clear parallels between citizen science and other participatory approaches, stemming in part from overlapping origins, and shared principles, aims, and methods. We also highlight distinctive features of citizen science when compared to these existing approaches, including: the importance of reciprocity; flexibility in the nature and extent of engagement with communities; and methodological neutrality in how citizen science approaches are applied in practice, which public health initiatives could better capitalise on. We argue wider use of citizen science principles and quality criteria in guiding the design and appraisal of citizen science initiatives in public health is necessary to strengthen the processes and outcomes of these initiatives. Further delineating the boundaries around citizen science and how it intersects with similar approaches is critical for the ongoing development and legitimation of citizen science in public health.